Laboratory characterization of relative humidity dependent properties for plasters - Ranesi, Alessandra (2021)
Funding Information: Funding: This research was founded by Portuguese Foundation for Science and Technology: PD/BD/150399/2019 – 1st author Doctoral Training Programme EcoCoRe - and UIDB/04378/2020 - Civil Engineering Research and Innovation for Sustainability Unit-CERIS.